2012
DOI: 10.1002/jcb.24109
|View full text |Cite
|
Sign up to set email alerts
|

TSA‐induced JMJD2B downregulation is associated with cyclin B1‐dependent survivin degradation and apoptosis in LNCap cells

Abstract: Histone deacetylase (HDAC) inhibitors are emerging as a novel class of anti-tumor agents and have manifested the ability to induce apoptosis of cancer cells, and a significant number of genes have been identified as potential effectors responsible for HDAC inhibitor-induced apoptosis. However, the mechanistic actions of these HDAC inhibitors in this process remain largely undefined. We here report that the treatment of LNCap prostate cancer cells with HDAC inhibitor trichostatin A (TSA) resulted in downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…In vitro studies have shown that the depletion of JMJD2B impairs cell growth progression and promotes cell apoptosis in gastric and breast cancer cells. Additionally, the downregulation of JMJD2B induced by trichostatin A (TSA) has been shown to induce cell apoptosis via the promotion of Cyclin B1‐dependent survivin degradation in prostate cancer cells . Consistent with these results, we provide further evidence that a disruption of JMJD2B in CRC cells inhibited cell proliferation and cell cycle progression but induced cell apoptosis .…”
Section: Introductionsupporting
confidence: 83%
“…In vitro studies have shown that the depletion of JMJD2B impairs cell growth progression and promotes cell apoptosis in gastric and breast cancer cells. Additionally, the downregulation of JMJD2B induced by trichostatin A (TSA) has been shown to induce cell apoptosis via the promotion of Cyclin B1‐dependent survivin degradation in prostate cancer cells . Consistent with these results, we provide further evidence that a disruption of JMJD2B in CRC cells inhibited cell proliferation and cell cycle progression but induced cell apoptosis .…”
Section: Introductionsupporting
confidence: 83%
“…A recent study shows that selective inhibition of HDAC2 by SAHA induces survivin downregulation in p53-dependent manner through MDM2 proteasomal degradation [187]. In prostate cancer cells, TSA treatment induced apoptosis, which is mediated by Cyclin B1/Cdc2-dependent degradation of survivin protein [188]. A clinical trial was conducted using SAHA in combination with fluorouracil, irinotecan hydrochloride and leucovorin calcium with the purpose to evaluate the safety and efficacy of SAHA along with these drugs in phase I and phase II, and to study alterations in TGF-β signaling and survivin expression (Table 2).…”
Section: Therapeutic Targeting Of Survivinmentioning
confidence: 99%
“…Thus, HDACs are important targets for therapeutic intervention in both hematological and solid malignancies (Ellis and Pili, 2010). HDAC inhibitors, which are emerging as a new class of anti-cancer agents, were shown to have anti-proliferation, pro-differentiating, and pro-apoptotic properties in cancer cells, including prostate cancer cells (Zhu et al, 2012). Among the well-established HDAC inhibitors, trichostatin A (TSA) represents the hydroxamic acids, which show general inhibition of class 1, 2, and 4 HDACs with nanomolar potency (Chang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%